Complete Genome Sequences of Escherichia coli Phages vB_EcoM-EP75 and vB_EcoP-EP335 - van Mierlo, Joël (Microbiol Resour Announc, 2019)
Phages vB_EcoM-EP75 (EP75) and vB_EcoP-EP335 (EP335) specifically infect Shiga toxin (Stx)-producing Escherichia coli (STEC) O157 strains. EP75 has a genome size of 158,143 bp and belongs to the genus Vi1virus. The genome size of EP335 is 76,622 bp, and it belongs to the genus Phieco32virus.